Religious Character Education in the Hijrah Community in Manado as a Muslim Minority Region - Mardan Umar; Feiby Ismail; Zainal Arifin (AL-ISHLAH: Jurnal Pendidikan, 2022)
The development of religious character is not only within the scope of formal education but must target non-formal education, such as in the hijrah community. The phenomenon of the hijrah community now dominates the da'wah movement in various cities, including Manado as a Muslim minority city. This study aims to determine religious character education in the hijrah community and its activities in Manado. This study uses a descriptive method with a qualitative approach and qualitative content analysis techniques. This study indicates that religious character education in the hijrah community is carried out by learning activities about basic knowledge of Islam and social activities. The findings of this study also show that the hijrah community in Manado carries out social activities by collaborating religious values with the values of local wisdom.